Electrophysiological resting-state signatures link polygenic scores to general intelligence - Englert, Rebecca; Stammen, Christina; Arnau, Stefan; Schneider Penate, Javier; Metzen, Dorothea; Digutsch, Jan; Gajewski, Patrick D.; Getzmann, Stephan; Fraenz, Christoph; Reinders, Jörg; Voelkle, Manuel C.; Streit, Fabian; et al. (Scientific reports, 2025)
Intelligence is associated with important life outcomes. Behavioral, genetic, structural, and functional brain correlates of intelligence have been studied for decades, but questions remain as to how genetics are related to trait expression and what intermediary role brain properties play. This study investigated these mediations in a representative sample of 434 individuals, comprising young and older adults. Polygenic scores (PGS) for intelligence were calculated. Resting-state EEG recordings were analyzed using graph theory quantifying functional connectivity across different frequencies. We tested whether global and local graph metrics like efficiency and clustering mediated the association between PGS and intelligence. PGS significantly predicted variance in intelligence and were related to frequency-specific graph metrics in areas predominantly located in parieto-frontal regions, which in turn were associated with intelligence. These findings, based on the first study linking PGS to intelligence using EEG-derived graph metrics, identify candidate pathways through which genetic variation may shape intelligence, providing a foundation for future hypothesis-driven investigations. Data for this study were collected as part of the Dortmund Vital Study (https://www.researchprotocols.org/2022/3/e32352; ClinicalTrials.gov: NCT05155397).
Gesehen am 26.01.2026